Hypoventilation trainings combined with physical exercises and their influences on person's functional state in physical work to failure - N. A. Fudin; S. Ya. Klassina; S. N. Pigareva; Y. E. Vagin (National Electronic Information Consortium (NEICON), 2020)
Objective: to study the influence of hypoventilation's trainings combined with physical exercises on the person's functional state and its physical working capacity in physical work to failure. Materials and methods: 18 young men were examined, and it were divided into 2 groups: main (12 persons) and control (6 persons). Only subjects of the main group were studied to hypoventilation breathing in combination with physical exercises. Before and after the training all subjects performed load testing on a bicycle ergometer to failure under ECG, pneumogram and EMG monitoring. Results: hypoventilation breathing combined with physical exercises was increased the work's time to failure from 165,1±25,6 to 307,3±52,0 s (p